Accessing In Situ Photocorrosion under Realistic Light Conditions: Photoelectrochemical Scanning Flow Cell Coupled to Online ICP-MS - Jenewein, Ken; Kormányos, Attila; Knöppel, Julius; Mayrhofer, Karl; Cherevko, Serhiy (ACS Measurement Science Au, 2021)
High-impact photoelectrode materials for photoelectrochemical (PEC) water splitting are distinguished by synergistically attaining high photoactivity and stability at the same time. With numerous efforts toward optimizing the activity, the bigger challenge of tailoring the durability of photoelectrodes to meet industrially relevant levels remains. In situ photostability measurements hold great promise in understanding stability-related properties. Although different flow systems coupled to light-emitting diodes were introduced recently to measure time-resolved photocorrosion, none of the measurements were performed under realistic light conditions. In this paper, a photoelectrochemical scanning flow cell connected to an inductively coupled plasma mass spectrometer (PEC-ICP-MS) and equipped with a solar simulator, Air Mass 1.5 G filter, and monochromator was developed. The established system is capable of independently assessing basic PEC metrics, such as photopotential, photocurrent, incident photon to current efficiency (IPCE), and band gap in a high-throughput manner as well as the in situ photocorrosion behavior of photoelectrodes under standardized and realistic light conditions by coupling it to an ICP-MS. Polycrystalline platinum and tungsten trioxide (WO3) were used as model systems to demonstrate the operation under dark and light conditions, respectively. Photocorrosion measurements conducted with the present PEC-ICP-MS setup revealed that WO3 starts dissolving at 0.8 VRHE with the dissolution rate rapidly increasing past 1.2 VRHE, coinciding with the onset of the saturation photocurrent. The most detrimental damage to the photoelectrode is caused when subjecting it to a prolonged high potential hold, e.g., at 1.5 VRHE. By using standardized illumination conditions such as Air Mass 1.5 Global under 1 Sun, the obtained dissolution characteristics are translatable to actual devices under realistic light conditions. The gained insights can then be utilized to advance synthesis and design approaches of novel PEC materials with improved photostability.
CRIS-Team Scopus Importer:2023-03-29
Keywords: ICP-MS; photocorrosion; photoelectrochemistry; scanning flow cell; solar simulator

CrOx-Mediated Performance Enhancement of Ni/NiO-Mg:SrTiO3in Photocatalytic Water Splitting - Han, Kai; Haiber, Diane M.; Knöppel, Julius; Lievens, Caroline; Cherevko, Serhiy; Crozier, Peter; Mul, Guido; Mei, Bastian (ACS Catalysis, 2021)
By photodeposition of CrOx on SrTiO3-based semiconductors doped with aliovalent Mg(II) and functionalized with Ni/NiOx catalytic nanoparticles (economically significantly more viable than commonly used Rh catalysts), an increase in apparent quantum yield (AQYs) from ∼10 to 26% in overall water splitting was obtained. More importantly, deposition of CrOx also significantly enhances the stability of Ni/NiO nanoparticles in the production of hydrogen, allowing sustained operation, even in intermittent cycles of illumination. In situ elemental analysis of the water constituents during or after photocatalysis by inductively coupled plasma mass spectrometry/optical emission spectrometry shows that after CrOx deposition, dissolution of Ni ions from Ni/NiOx-Mg:SrTiO3 is significantly suppressed, in agreement with the stabilizing effect observed, when both Mg dopant and CrOx are present. State-of-the-art electron microscopy and energy-dispersive X-ray spectroscopy (EDX) and electron energy-loss spectroscopy (EELS) analyses demonstrate that upon preparation, CrOx is photodeposited in the vicinity of several, but not all, Ni/NiOx particles. This implies the formation of a Ni-Cr mixed metal oxide, which is highly effective in water reduction. Inhomogeneities in the interfacial contact, evident from differences in contact angles between Ni/NiOx particles and the Mg:SrTiO3 semiconductor, likely affect the probability of reduction of Cr(VI) species during synthesis by photodeposition, explaining the observed inhomogeneity in the spatial CrOx distribution. Furthermore, by comparison with undoped SrTiO3, Mg-doping appears essential to provide such favorable interfacial contact and to establish the beneficial effect of CrOx. This study suggests that the performance of semiconductors can be significantly improved if inhomogeneities in interfacial contact between semiconductors and highly effective catalytic nanoparticles can be resolved by (surface) doping and improved synthesis protocols.
CRIS-Team Scopus Importer:2021-09-17
Keywords: co-catalyst; in situ ICP-MS; photocatalytic water splitting; SrTiO; stability

Dissolution of WO3 modified with IrOx overlayers during photoelectrochemical water splitting - Jenewein, Ken; Knöppel, Julius; Hofer, André; Kormanyos, Attila; Mayerhöfer, Britta; Speck, Florian; Bierling, Markus; Thiele, Simon; Bachmann, Julien; Cherevko, Serhiy (SusMat, 2023)
WO3, an abundant transition metal semiconductor, is one of the most discussed materials to be used as a photoanode in photoelectrochemical water-splitting devices. The photoelectrochemical properties, such as photoactivity and selectivity of WO3 in different electrolytes, are already well understood. However, the understanding of stability, one of the most important properties for utilization in a commercial device, is still in the early stages. In this work, a photoelectrochemical scanning flow cell coupled to an inductively coupled plasma mass spectrometer is applied to determine the influence of co-catalyst overlayers on photoanode stability. Spray-coated WO3 photoanodes are used as a model system. Iridium is applied to the electrodes by atomic layer deposition in controlled layer thickness, as determined by ellipsometry and x-ray photoelectron spectroscopy. Photoactivity of the iridium-modified WO3 photoanodes decreases with increasing iridium layer thickness. Partial blocking of the WO3 surface by iridium is proposed as the main cause of the decreased photoelectrochemical performance. On the other hand, the stability of WO3 is notably increased even in the presence of the thinnest investigated iridium overlayer. Based on our findings, we provide a set of strategies to synthesize nanocomposite photoelectrodes simultaneously possessing high photoelectrochemical activity and photostability.<br

IrO2 coated TiO2 core-shell microparticles advance performance of low loading proton exchange membrane water electrolyzers - Pham, Chuyen Van; Bühler, Melanie; Knöppel, Julius; Bierling, Markus; Seeberger, Dominik; Escalera-López, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Thiele, Simon; Thiele, Simon (Applied Catalysis B-Environmental, 2020)
Herein we present novel IrO2 coated TiO2 core-shell microparticles (IrO2@TiO2) as an oxygen evolution reaction catalyst. We compare the IrO2@TiO2 catalyst to commercial TiO2 supported IrO2 catalyst (IrO2/TiO2) and pure IrO2 catalyst powder. A stability analysis via on-line inductively coupled plasma mass spectrometry based on the S-number, a descriptor considering both energy efficiency and catalyst utilization efficiency, shows that the IrO2@TiO2 catalyst shows high potential for practical applications. This was further confirmed by full-cell tests showing superior performance of the IrO2@TiO2 catalyst with moderate and low loadings of 1.2 mgIr cm−2 and 0.4 mgIr cm−2, respectively. The core-shell catalyst is synthesized via facile route suitable for large quantities. Moreover, stable inks from the synthesized catalyst powder make this system appealing for large scale manufacturing of cells. Given the facile synthesis route, high activity, and good stability, the IrO2@TiO2 catalyst is potentially suitable for industry proton exchange membrane water electrolysis application.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Core shell catalyst; Iridium oxide catalyst; Oxygen evolution reaction; Proton exchange membrane; Water electrolysis

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells - Knöppel, Julius; Möckl, Maximilian; Escalera-López, Daniel; Stojanovski, Kevin; Bierling, Markus; Böhm, Thomas; Thiele, Simon; Rzepka, Matthias; Cherevko, Serhiy (Nature Communications, 2021)
Recent research indicates a severe discrepancy between oxygen evolution reaction catalysts dissolution in aqueous model systems and membrane electrode assemblies. This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolution is studied in an aqueous model system, a scanning flow cell coupled to an inductively coupled plasma mass spectrometer. Real dissolution rates of the Ir OER catalyst in membrane electrode assemblies are measured with a specifically developed, dedicated setup. Overestimated acidity in the anode catalyst layer and stabilization over time in real devices are proposed as main contributors to the dissolution discrepancy. The results shown here lead to clear guidelines for anode electrocatalyst testing parameters to resemble realistic electrolyzer operating conditions.
CRIS-Team Scopus Importer:2021-04-30

Photocorrosion of WO3 Photoanodes in Different Electrolytes - Knöppel, Julius; Kormanyos, Attila; Mayerhöfer, Britta; Hofer, André; Bierling, Markus; Bachmann, Julien; Thiele, Simon; Cherevko, Serhiy (ACS Physical Chemistry Au, 2021)
Photocorrosion of an n-type semiconductor is anticipated to be unfavorable if its decomposition potential is situated below its valence band-edge position. Tungsten trioxide (WO3) is generally considered as a stable photoanode for different photoelectrochemical (PEC) applications. Such oversimplified considerations ignore reactions with electrolytes added to the solvent. Moreover, kinetic effects are neglected. The fallacy of such approaches has been demonstrated in our previous study dealing with WO3 instability in H2SO4. In this work, in order to understand parameters influencing WO3 photocorrosion and to identify more suitable reaction environments, H2SO4, HClO4, HNO3, CH3O3SH, as electrolytes are considered. Model WO3 thin films are fabricated with a spray-coating process. Photoactivity of the samples is determined with a photoelectrochemical scanning flow cell. Photostability is measured in real time by coupling an inductively coupled plasma mass spectrometer to the scanning flow cell to determine the photoanode dissolution products. It is found that the photoactivity of the WO3 films increases as HNO3 < HClO4 ≈ H2SO4 < CH3O3SH, whereas the photostability exhibits the opposite trend. The differences observed in photocorrosion are explained considering stability of the electrolytes toward decomposition. This work demonstrates that electrolytes and their reactive intermediates clearly influence the photostability of photoelectrodes. Thus, the careful selection of the photoelectrode/electrolyte combination is of crucial importance in the design of a stable photoelectrochemical water-splitting device.
Keywords: Photocorrosion; Tungsten oxide; Photostability; Water splitting; Electrode kinetics

Platinum Dissolution in Realistic Fuel Cell Catalyst Layers - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Angewandte Chemie International Edition, 2021)
Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real-world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half-cell with inductively coupled plasma mass spectrometry (ICP-MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re-deposition and equilibrium potential.
CRIS-Team WoS Importer:2021-03-12